(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In recent years worldwide, the manufacturing and consumption of functional foods have augmented importantly. Dairy products are nutritive and highly consumed while functional foods improve consumer health. A Mozzarella cheese added with agavin, was formulated, prepared, characterized and studied in order to know its properties, influenced by three variables concentration of agavin as a prebiotic component, pre-acidification as part of the manufacturing process and storage time. The effect of each variable was different, the incorporation of agavin (0.7- 3.3) improved the nutritional value (fiber) and properties such as luminosity, texture and elasticity. The preacidification (0.0375) stage augmented the acidity and improved some functional and physical properties. Both variables did not influence acceptation by the consumer, thus the assessed cheese samples had good sensory scores. Whereas the storage time (1, 11, 21 and 31 days) in which the properties were analyzed, recorded a decreasing trend in moisture content and pH, with low net color changes, and variable changes in texture.